Technology-based pragmagogy competency assessment to measure teachers' ability in classroom management - Muhammad Rohmadi; Memet Sudaryanto; Harun Joko Prayitno; Hasan Zainnuri (Jurnal Cakrawala Pendidikan, 2023)
Teachers' classroom management skills can be seen in their language teaching skills. This study aimed to (1) develop an online assessment model to measure teachers' pragmagogy ability in Indonesia and (2) measure teachers' ability to respond to pragmagogy-related stimuli. This study uses a DD approach to answer the problem formulation determined during model design, development, and evaluation. The sample included 3,150 primary, secondary, and advanced Indonesian teachers. Functionality, reliability, usability, efficiency, maintainability, and portability were validated. This study explained the formulated pragmagogy construction through exploratory factor analysis. Stress testing and installation testing were used to broaden the application's reach. Based on the initial analysis, the online assessment model concludes that the teacher's pragmagogy ability can determine knowledge, skills, and attitudes. Teachers' pragmagogy ability can be determined through pedagogic knowledge as the framework for roles and figures in the form of thinking; reflective and emotional intelligence; ability in instructional communication patterns; and other aspects to realize pragmagogic competence. The use of pragmagogy measurement applications can examine various approaches chosen by teachers to maximize the teaching-learning process in the classroom through interactive, responsive, persuasive, implicative, locution, illocution, perlocution approaches to describe the pragamagogical competencies possessed by teachers in classroom management that is interesting and fun for their students.